Pengaruh Jumlah Komite Audit Dan Rapat Komite Audit Terhadap Internal Fraud Yang Terjadi di Perbankan (Bank Umum Syariah) Periode 2018-2021 - Dinda Sukma Noprianti Putri; Mohammad Orinaldi; Khairiyani Khairiyani (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Fraud is related to fraudulent actions that are carried out intentionally and result in another party suffering losses. The main issue raised in this research is related to the large number of fraud cases that occur in Sharia Commercial Banks. The underlying reason for researching this issue is because, the majority of Sharia Commercial Banks have formed independent audit committees, held audit committee meetings, and given audit committee terms of service by referring to POJK N0.55/POJK.04/2015 concerning the Formation and Implementation Guidelines for Committee Work. Auditing. The formulation of the problem is whether the number of audit committees, audit committee meetings and the number of audit committees that occurs in banking, can it influence internal fraud that occurs in banking. With the aim of having audit committee meetings and the number of audit committees, it can minimize the risk of fraud in banking.This research is quantitative research, namely research based on the philosophy of positivism, used to research certain populations and samples, data collection using research instruments, data analysis is quantitative or statistical. Data analysis uses statistics by presenting data using tables. Because the data obtained in this research is in the form of financial report figures. The figures obtained will be analyzed further in data analysis, the data management process uses eviews 10.From the research results, it can be concluded that the variable number of audit committees has a significant effect on internal fraud in Islamic commercial banks in Indonesia for the 2018-2021 period. The Audit Committee Meeting variable has an insignificant negative effect on Internal Fraud in Sharia Commercial Banks in Indonesia for the 2018-2021 period. And the variables Number of Audit Committees and Audit Committee Meetings have a significant effecton Internal Fraud in Sharia Commercial Banks in Indonesia for the 2018-2021 period.